2010
DOI: 10.1038/jcbfm.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NR2A Receptors Induces Ischemic Tolerance through CREB Signaling

Abstract: Previous exposure to a nonlethal ischemic insult protects the brain against subsequent harmful ischemia. N-methyl-D-aspartate (NMDA) receptors are a highly studied target of neuroprotection after ischemia. Recently, NMDA receptor subtypes were implicated in neuronal survival and death. We focused on the contribution of NR2A and cyclic-AMP response element (CRE)-binding protein (CREB) signaling to ischemic tolerance using primary cortical neurons. Ischemia in vitro was modeled by oxygen-glucose deprivation (OGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 42 publications
3
53
2
Order By: Relevance
“…We demonstrate for the first time that the upregulation of TDP-43 is mediated by the activation of NR2AR after glutamate accumulation. Recent evidence shows that NR2AR activation promotes neuronal survival in acute CNS injury such as cerebral ischemia and traumatic spinal injury (Alilain and Goshgarian, 2008;Liu et al, 2007;Terasaki et al, 2010). However, the underlying mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate for the first time that the upregulation of TDP-43 is mediated by the activation of NR2AR after glutamate accumulation. Recent evidence shows that NR2AR activation promotes neuronal survival in acute CNS injury such as cerebral ischemia and traumatic spinal injury (Alilain and Goshgarian, 2008;Liu et al, 2007;Terasaki et al, 2010). However, the underlying mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that several studies have indicated that NMDA receptor subtypes differ in their ability to cause cell death. GluN2B-containing NMDA receptors initiate cell death, whereas GluN2A-containing receptors have been reported to contribute to neuroprotection signaling in traumatic mechanical injury and ischemia models ( jpet.aspetjournals.org Terasaki et al, 2010). This may correspond to an enrichment of GluN2A and GluN2B subunits in synaptic and extrasynaptic compartments, respectively (Tovar and Westbrook, 1999;Lozovaya et al, 2004), and the ability of synaptic NMDA receptors to promote neuroprotection, whereas extrasynaptic NMDA receptor activation signals to neuronal cell death (Hardingham and Bading, 2003;Papadia et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One intriguing possibility is that the potentiation of synaptic NMDA receptors containing the GluN2A subunit may stimulate neuroprotective-signaling pathways Terasaki et al, 2010). In an in vivo context, direct agonist activation would activate inappropriate receptors, whereas a potentiator should specifically increase the response of endogenously activated receptors, thus enhancing an appropriate biological response.…”
Section: Discussionmentioning
confidence: 99%
“…MCAO in male mice led to a spike in pAMPK levels 4 h after IPC and reduction after 72 h, suggesting that downregulation of AMPK contributes toward delayed PC [91]. Finally, the roles of many key players like HIF-2α, SIRT1, and CREB suspected of being part of the preconditioning cascade are now established [85,92,93].…”
Section: Enzymes and Receptorsmentioning
confidence: 92%